BM25 Algorithm for Improving Academic Website Search Accuracy: Algoritma BM25 untuk Meningkatkan Akurasi Pencarian di Situs Web Akademik - Glenn David Paulus Maramis; Marthasya Chantika Putri Ranti; Kristofel Santa (Indonesian Journal of Innovation Studies, 2026)
General Background: The increasing volume of digital information in academic environments requires search systems that can deliver accurate and relevant results. Specific Background: The Faculty of Engineering UNIMA website still relies on simple keyword matching, which often produces irrelevant outputs and reduces the effectiveness of information access. Knowledge Gap: Although the BM25 algorithm is widely recognized for its superior relevance scoring in information retrieval, its application in faculty-level academic portals remains limited. Aims: This study aims to implement the BM25 algorithm using Meilisearch integrated with Laravel and Filament to improve search relevance, speed, and data management efficiency. Results: The implemented system successfully ranks the most relevant documents at the top with response times measured in milliseconds, and automatic index synchronization ensures consistent and up-to-date search results. Novelty: This research presents one of the first BM25-based search implementations within an Indonesian faculty website, integrating Laravel, Meilisearch, and Filament into a cohesive architecture. Implications: The findings show that BM25 significantly enhances the quality of search services and user experience, providing a scalable model for academic institutions seeking effective information retrieval solutions. Highlights: Enhances search relevance and speed on a faculty academic website using BM25. Integrates Laravel, Meilisearch, and Filament into a unified, easy-to-manage system. Offers a scalable model for improving information access in higher education portals. Keywords: BM25, Information Retrieval, Meilisearch, Laravel, Academic Website